Investigating the use of a hybrid plasmonic–photonic nanoresonator for optical trapping using finite-difference time-domain method - Mossayebi, M.; Wright, Amanda J.; Parini, A.; Somekh, Michael G. (Springer, 2016)
We investigate the use of a hybrid nanoresonator comprising a photonic crystal (PhC) cavity coupled to a plasmonic bowtie nanoantenna (BNA) for the optical trapping of nanoparticles in water. Using finite difference time-domain simulations, we show that this structure can confine light to an extremely small volume of ~30,000 nm3 (~30 zl) in the BNA gap whilst maintaining a high quality factor (5400–7700). The optical intensity inside the BNA gap is enhanced by a factor larger than 40 compared to when the BNA is not present above the PhC cavity. Such a device has potential applications in optical manipulation, creating high precision optical traps with an intensity gradient over a distance much smaller than the diffraction limit, potentially allowing objects to be confined to much smaller volumes and making it ideal for optical trapping of Rayleigh particles (particles much smaller than the wavelength of light).